The “Ball in Basket” Technique for Tibiotalocalcaneal Fusion - Giaretta, Stefano; Micheloni , Gian Mario; Mazzi , Michele; Lunardelli , Enrico; Ambrosini , Carlo; Rebeccato , Arturo (Acta Biomedica Atenei Parmensis, 2020)
Tibiotalocalcaneal arthrodesis (TTCA) in severe bone deficit represents a complex challenge for expertorthopedic surgeons also. This study aims to illustrate a surgical technique, defined as “ball in basket”, that facilitates the fitting of the structural bone graft (femoral head from bone bank) and its placement, in order to fill the bone gap during instrumented arthrodesis. The proposed technique includes the preparation of the recipient bone surfaces with acetabular convex reamers and of concave reamers to shape the bone graft from bone bank. This preparation guarantees a maximum congruence of the bone surfaces and a greater stability of the bone graft during the placement of the fixation devices to optimize the bone fusion and to provide a good patient clinical outcome. The preliminary results obtained for two patients, initially presenting with severe anatomical deformity associated with severe bone gap, are described. Patients underwent clinical and radiographic follow-up evaluations (respectively at 4 and 30 months of follow-up) showing radiographic healing and good functional recovery. The results are encouraging, although long-term studies and a wider cohort of patients are necessary to consider this technique a reliable aid in case of severe bone deficit. (www.actabiomedica.it)